Development Strategy of Sustainable Beef Cattle - Salendu, Artise H.S.; Lumenta, Ingriet D.R.; Elly, Femi Hadidjah; Leke, Jein Rinny; Syarifuddin, Syarifuddin; Polakitan, Derek (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
Â The purpose of developing beef cattle farming is to increase the population and productivity of cattle products followed by increasing farmersâ€™ income, creating jobs and improving the genetic quality of beef cattle. The problem is that beef cattle farms in North Sulawesi are carried out in traditional management instead of eco-friendly; they are mostly developed by grazing on agricultural land. This study aims to identify the potential strategies to support the development of eco-friendly beef cattle farms. This study used a survey to analyze the role, opportunities and challenges of beef cattle farms in North Bolaang Mongondow Regency. The locations were purposively sampled to include the central area for government-initiative beef cattle development i.e. Sangkub, Bintauna and East Bolangitan districts. The data were subject to internal and external analysis using IFAS matrix, EFAS matrix and SWOT analysis.The results showed that the actual beef cattle population could be increased to 1.37 times. Development is carried out with an orientation to environment and sustainability using LEISA concept. The development of beef cattle was in a condition dominated by strength (the strength value of 1.882 or 76.59%). Opportunities are more quickly responded in the face of the threat of beef cattle development (the opportunity value of 1.842 or 68.09%). In conclusion, the development of beef cattle has a role in increasing the income of farmers and has market opportunities and the challenges can be minimized by increasing the productivity and quality of beef cattle that are environmentally oriented. Technology introduction is needed for the development of sustainable beef cattle farms.